SOLUSI MENGATASI HAMBATAN KOMUNIKASI BERAGAMA DI DAERAH MAYORITAS KARO - Mirandha W. Lubis, Mhd Rifai Luthfi (Program Studi Pendidikan Islam Pascasarjana UIN Sumatera Utara Medan, 2021)
Abstract: Indonesia is known as a diversity of tribes, ethnicities and religions proving that Indonesia is a pluralistic society. This can be a very pluralistic potential, with various nuances of real pluralism in various ethnic groups with specific backgrounds: regional languages, traditions, customs, arts, culture and religion. Seeing the reality of a pluralistic Indonesian nation and the importance of inter-religious dialogue being carried out, the authors, using the research method of library research, took the theme of writing: